Extraction of Polyphenols from Horn Banana Peel (Musa Paradisiaca var. Typica) Using the Ultrasound Assisted Extraction Method - Sugesta, Muhammad Yongki Ivan; Wibowo, Revi Setia; Alfiah, Masrurotul; Reza, Muhammad; Achmad Sjaifullah (Program Studi Teknik Kimia Universitas Jember, 2024)
Banana peel contains starch, protein, fat, total fiber, unsaturated fatty acids, pectin, amino acids, polyphenols and micronutrients. Horn banana peelhas many benefits, namely it can be processed into a natural antioxidant material that can minimize banana skin waste. The banana peel extraction method used is Ultrasound Assisted Extraction. Ultrasound Assisted Extraction at optimal conditions produces good levels of total polyphenols with a short extraction time. In the use of ultrasonic no additional chemicals or other materials are needed. This study aims to determine the effect of extraction time (10, 20, 30 minutes), extraction temperature (20, 30, 40℃) and solvent ratio (gr/mL) (1:25, 1:30, 1:35) on polyphenols. The Design Expert V13 program with Response Surface Methodology (RSM) Box-Behnken Design (BBD) was used to determine the combination of extraction parameters that lead to optimal results for total polyphenol content. Based on the research that has been done, it can be stated that the extraction parameters affect the total polyphenol content. The highest total polyphenol content was 61,007 mg GAE/g sample with the extraction conditions at an extraction temperature of 30℃, an extraction time of 30 minutes, and a ratio of banana peel powder to a dissolution of 1:30 g/mL. Keywords : Banana Peel, Polyphenols, Ultrasound Assisted Extraction